The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1161/01.cir.69.3.605
|View full text |Cite
|
Sign up to set email alerts
|

Coronary thrombolysis with intravenously administered human tissue-type plasminogen activator produced by recombinant DNA technology.

Abstract: Coronary thrombolysis was induced by intravenous infusion of human tissue-type plasminogen activator (recombinant human t-PA or rt-PA) obtained by expression of the cloned gene in a mammalian cell system. Thrombolysis was detected by the appearance of reperfusion arrhythmia and confirmed by repeat angiography in anesthetized dogs with 1-hr-old thrombi of the left anterior descending coronary artery that were induced with a copper coil. Infusion of 1000 IU (10 ,ug)/kg/min intravenous rt-PA (n = 9) elicited repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

1984
1984
2002
2002

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 183 publications
(46 citation statements)
references
References 11 publications
1
43
0
2
Order By: Relevance
“…The infusion of rt-PA was not associated with systemic activation of the fibrinolytic system or with clinically evident bleeding. In the 24 dogs that received rt-PA and completed the study, fibrinogen levels before and after infusion were nearly identical ( figure 1. The infarct size in reperfused dogs (groups I to IV) was significantly smaller than in the dogs with persistent coronary artery occlusion (groups V and VI).…”
Section: Methodsmentioning
confidence: 92%
“…The infusion of rt-PA was not associated with systemic activation of the fibrinolytic system or with clinically evident bleeding. In the 24 dogs that received rt-PA and completed the study, fibrinogen levels before and after infusion were nearly identical ( figure 1. The infarct size in reperfused dogs (groups I to IV) was significantly smaller than in the dogs with persistent coronary artery occlusion (groups V and VI).…”
Section: Methodsmentioning
confidence: 92%
“…26 The infusion rates of proUK and tPA used in the present study were previously shown in a coronary thrombosis model to be both effective and fibrin specific in dogs. 23,24 Because the lysis properties of M5 in vitro and in vivo were comparable and reflect the catalytic changes induced by the mutation, it seems likely that these properties will also be seen in other clot lysis models.…”
Section: Discussionmentioning
confidence: 99%
“…Then an intravenous infusion of saline or activator was started. Infusion rates of proUK (20 g/kg per minute) or tPA (10 g/kg per minute), which have been reported in the literature to be both effective and fibrin-specific in dogs, 23,24 were used. The tPA infusion was limited to 60 minutes because of its high cost.…”
Section: Clot Lysis In Anesthetized Dogsmentioning
confidence: 99%
“…With addition of t-PA after thrombin-coagulation in euglobulin fractions and in whole plasma samples, the response to a given concentration of exogenous t-PA was diminished (figure 2) Results are for t-PA antigen activity (n 316 analyses).…”
Section: Methodsmentioning
confidence: 99%